2020
DOI: 10.3389/fimmu.2020.01163
|View full text |Cite
|
Sign up to set email alerts
|

H60: A Unique Murine Hematopoietic Cell-Restricted Minor Histocompatibility Antigen for Graft-versus-Leukemia Effect

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an important treatment for many types of hematological malignancies. Matching of donor and recipient for the major histocompatibility complex (MHC) improves the HSCT reconstitution, but donor-derived T cells reactive to non-MHC encoded minor histocompatibility antigens (MiHAs) can induce graft-versus-host disease (GVHD) while also being needed for graft-versus-leukemia (GVL) effects. MiHAs are allelically variant self-peptides presented conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Using mass spectrometry, we validated a total of 24 novel GvL mHAs, an increase from the 13 GvL mHAs that have been discovered since Els Goulmy et al reported the first discovered GvL mHA, HA-1, in 1983 1,25,28,[30][31][32][33] . The 16 novel GvL mHAs found for HLA-A*02:01 together cover 98.8% of HLA-A*02:01-positive patients in the DISCOVeRY-BMT dataset, the three for HLA-B*35:01 cover 60.7% of HLA-B*35-:01-positive DISCOVeRY-BMT patients, and the five for HLA-C*07:02 cover 78.9% of HLA-C*07:02-positive DISCOVeRY-BMT patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Using mass spectrometry, we validated a total of 24 novel GvL mHAs, an increase from the 13 GvL mHAs that have been discovered since Els Goulmy et al reported the first discovered GvL mHA, HA-1, in 1983 1,25,28,[30][31][32][33] . The 16 novel GvL mHAs found for HLA-A*02:01 together cover 98.8% of HLA-A*02:01-positive patients in the DISCOVeRY-BMT dataset, the three for HLA-B*35:01 cover 60.7% of HLA-B*35-:01-positive DISCOVeRY-BMT patients, and the five for HLA-C*07:02 cover 78.9% of HLA-C*07:02-positive DISCOVeRY-BMT patients.…”
Section: Discussionmentioning
confidence: 97%
“…The copyright holder for this preprint this version posted August 15, 2022. ; https://doi.org/10.1101/2022.08.12.503667 doi: bioRxiv preprint cell responses against them will lead to GvL effects without GvHD. Approximately 55 mHAs have been reported to date, including 13 validated GvL mHAs, and clinical trials of mHA-targeted cellular immunotherapies and vaccines have been performed [25][26][27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 The immunogenicity of the B6⇒C.B10 LN cell infusion model arises from mismatch at multiple minor H antigens, H60 being dominant. 52 , 53 , 54 , 55 Immune disparity between B6 and C.B10 mice also involves other minor antigens such as H4, H7, H13, and H28. 56 The attenuation of marrow failure by infusion of male G-MDSCs into female C.B10 BMF recipients showed that G-MDSC immunosuppression could overcome Y antigen disparity.…”
Section: Discussionmentioning
confidence: 99%